Ketamine‐Magnesium for Refractory Chronic Cluster Headache: A Case Series. Issue 10 (31st October 2020) - Moisset, Xavier; Giraud, Pierric; Meunier, Estelle; Condé, Sakahlé; Périé, Maud; Picard, Pascale; Pereira, Bruno; Ciampi de Andrade, Daniel; Clavelou, Pierre; Dallel, Radhouane
Abstract : Objectives: To evaluate the safety and efficacy of ketamine‐magnesium combination to reduce attacks in a series of patients with refractory chronic cluster headache (rCCH). Background: Refractory chronic cluster headache (CCH) is a rare but highly debilitating condition that needs new treatment options. A previous publication reported that a single infusion of ketamine‐magnesium combination was effective in 2 patients with rCCH. Methods: The treatment was proposed to consecutive patients with rCCH seen in 2 French hospitals between November 2015 and February 2020 and who were resistant to at least 3 preventive treatments. They received a single ketamine infusion (0.5 mg/kg over 2 hours) combined with magnesium sulfate (3000 mg). The main outcome was a comparison of the number of daily attacks 2 weeks prior to the ketamine‐magnesium infusion and 1 week after (on days 7 and 8). The second outcome was the percentage of responders (patients with ≥50% reduction in the frequency of daily attacks). Safety was assessed by the recording of adverse events during infusion. Descriptive statistics are presented as mean ± standard deviation. Results: Seventeen patients (14 men), with an age of 35.2 ± 8.1 years, were included. They presented with CCH for 6.6 ± 4.3 years. The number of daily attacks decreased from 4.3 ± 2.4 before treatment to 1.3 ± 1.0 after treatment (difference: −3.1 (95% CI: −4.5 to −1.6), P < .001). Seventy six percent (13/17) were responders. Transient and mild sedation was reported by 7/17 patients (41.2%). Conclusions: The ketamine‐magnesium combination seems an effective and well‐tolerated therapy for rCCH. Placebo‐controlled studies should be conducted to further confirm these findings.